I Think, Therefore I Add Value – Philosophy of Science as a Practical Tool for the Mine Geologist - J Vann (The Australasian Institute of Mining and Metallurgy, 2011)
The philosophical context of many activities in mine geology can be an important lever in adding value to operations. For mine geologists (including resource and grade control geologists) we argue that the tasks of problem formulation, observation and data collection, interpretation and modelling invoke various philosophical considerations whether the practitioner is aware of them or not.Constructing testable models to explain reality is the definitive aspect of any activity claiming to be ‘scientific’. A primary goal of mining geology is to build models that accurately predict reality to an acceptable degree and these include litho-structural, stratigraphic, grade control, resource or reconciliation models. What’s more, in mine geology we are often able collect additional drill samples or access new underground openings, for example, that can provide relatively rapid feedback on how predictive, and therefore useful, our models are. In this paper, we describe the key philosophical frameworks proposed for conducting scientific investigations, including falsification, the method of multiple working hypotheses and structural concepts of scientific theory. The strengths and weaknesses of these approaches are discussed and an attempt is made to relate them to activities undertaken by mine geologists. Common perceptions of what constitutes the scientific method have been dominated by how scientists do experimental physics and chemistry in particular. There are very important differences in the types of problem confronted in these experimental sciences compared to the ‘historical sciences’, such as geology, where the processes studied are unique and only evidential traces of past events are available. The philosophical implications of attempting to validate numerical geological models, such as resource estimates are also briefly considered.Some practical conclusions are drawn about how mine geology activities can be better implemented if practitioners are cognisant of the importance of philosophical considerations when attempting to gain new knowledge through a scientific investigation. We believe that the implications for creating additional value to a project or operation can be very significant when geology is applied by a practitioner with an understanding of the philosophical basis of the activities we think of as constituting a scientific investigation.Remember that all models are wrong; the practical question is how wrong do they have to be to not be useful? (Box and Draper, 1987, 74 p).The demand that theories be highly falsifiable has the attractive consequence that theories should be clearly stated and precise. If a theory is so vaguely stated that it is not exactly clear what it is claiming, then when tested by observation or experiment it can always be interpreted so as to be consistent with the results of the test. (Chalmers, 1999, 67 p).